2015
DOI: 10.1152/ajprenal.00429.2014
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II increases fibronectin and collagen I through the β-catenin-dependent signaling in mouse collecting duct cells

Abstract: Cuevas CA, Gonzalez AA, Inestrosa NC, Vio CP, Prieto MC. Angiotensin II increases fibronectin and collagen I through the ␤-catenin-dependent signaling in mouse collecting duct cells. Am J Physiol Renal Physiol 308: F358 -F365, 2015. First published November 19, 2014 doi:10.1152/ajprenal.00429.2014.-The contribution of angiotensin II (ANG II) to renal and tubular fibrosis has been widely reported. Recent studies have shown that collecting duct cells can undergo mesenchymal transition suggesting that collecting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 51 publications
2
46
0
Order By: Relevance
“…CD cells have the predisposition to epithelial–mesenchymal transition . We have shown that ANG II treatment stimulates fibronectin and collagen I, both markers of fibrosis, via β‐catenin pathway in M‐1 CD cells . Here we have shown that prorenin treatment at nanomlar concentrations induces ROS formation and enhance the expression of CTGF, α‐SMA, PAI‐I, fibronectin and collagen I, all markers of fibrosis (Figures and ).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…CD cells have the predisposition to epithelial–mesenchymal transition . We have shown that ANG II treatment stimulates fibronectin and collagen I, both markers of fibrosis, via β‐catenin pathway in M‐1 CD cells . Here we have shown that prorenin treatment at nanomlar concentrations induces ROS formation and enhance the expression of CTGF, α‐SMA, PAI‐I, fibronectin and collagen I, all markers of fibrosis (Figures and ).…”
Section: Discussionmentioning
confidence: 60%
“…We have demonstrated that chronic ANG II infusions increase CD renin and prorenin synthesis and secretion despite the suppression of renin expression in juxtaglomerular cells . In addition, we have shown that cultured CD cells undergo to epithelial–mesenchymal transition and have induced expression of fibronectin and collagen I after ANG II treatment …”
Section: Introductionmentioning
confidence: 83%
“…AngII enhances Wnt1 expression, β-catenin nuclear translocation in mouse podocytes, with inhibition of Wnt/β-catenin pathway attenuating podocyte injury (139). β-catenin destabilization reagent also inhibits AngII-induced β-catenin, collagen I, fibronectin and osteopontin in mouse collecting duct cell or kidney of renovascular hypertensive rat (140, 141). Thus, there is accumulating evidence indicating a close relationship between the Wnt/β-catenin pathway and AT1 receptor in regard to cardiovascular remodeling and chronic kidney diseases.…”
Section: Cascades Of Wnt Notch Hippo and Mitochondriamentioning
confidence: 99%
“…However, it has been shown that intratubular Ang II can also promotes tubular fibrosis (Ishidoya et al 1995) and that collecting duct cells have the predisposition to epithelial-mesenchymal transition (Ivanova et al 2008; Butt et al 2007). We demonstrated in vitro evidence that Ang II treatment of collecting duct cells stimulates fibronectin and collagen I, both markers of fibrosis, via β-catenin pathway (Cuevas et al 2014). Further studies are necessary to fully elucidate whether the stimulation of tubular fibrosis during intrarenal RAS activation is dependent or independent of an Ang II-mediated mechanism, i.e., the direct activation of the (P)RR by prorenin in the collecting duct.…”
Section: The (Pro)renin Receptor Cyclooxygenase-2 and Ras Activationmentioning
confidence: 99%